The Notion of "Big Data" and the New Evolution of Artificial Intelligence - Mateescu, Florina (Journal of Danubian Studies and Research, 2022)
It is no longer a novelty that more and more electronic devices are used, in general, and that production processes are becoming increasingly digitized. We find that vast amounts of data are generated every day in the economy, as well as through people's personal and social activities. Data is an important component in the European Union's digital transformation process. Artificial intelligence is based on "smart information", and its development depends on how this data will be managed in Europe. We want to capture the important aspects related to this topic, using the logical method, the comparative method, the sociological method. We will analyze, synthesize, compare the various legislative provisions, correlating them with technical explanations, so as to reveal the importance of artificial intelligence in contemporary society. Reading this study can be useful both for students and teachers, lawyers, magistrates and other legal professionals, but also for those who are not in the field, but want to document themselves on the presented topic. The novelty element of our study will consist in merging the technical and legal notions proposed by the European Union, in an own interpretation and in a personal vision, so that the topicality of this subject emerges.